2021
DOI: 10.12968/jowc.2021.30.sup5.s7
|View full text |Cite
|
Sign up to set email alerts
|

Topical oxygen therapy in the treatment of diabetic foot ulcers: a multicentre, open, randomised controlled clinical trial

Abstract: Objectives: Perfusion and blood oxygen levels are frequently insufficient in patients with hard-to-heal wounds due to poor circulation, vascular disruption and vasoconstriction, reducing the wound's capacity to heal. This study aimed to investigate the effect of topical oxygen on healing rates in patients with hard-to-heal diabetic foot ulcers (DFUs) (i.e., non-responsive over four weeks). Method: This multicentre, open-label, community-based randomised clinical trial compared standard care (SOC) with or witho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
54
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(54 citation statements)
references
References 18 publications
0
54
0
Order By: Relevance
“…The increased ROS levels appear to accelerate the signaling processes without causing any damage at the cellular level. On a clinical level, studies have shown comparable or decreased adverse events and hospitalizations compared to standard of care with no supplemental oxygen [38][39][40][41].…”
Section: Molecular Biomarkers In Growth Factor Signaling Transductionmentioning
confidence: 99%
“…The increased ROS levels appear to accelerate the signaling processes without causing any damage at the cellular level. On a clinical level, studies have shown comparable or decreased adverse events and hospitalizations compared to standard of care with no supplemental oxygen [38][39][40][41].…”
Section: Molecular Biomarkers In Growth Factor Signaling Transductionmentioning
confidence: 99%
“…Partially conducted amid the coronavirus pandemic, this study had a 19% withdrawal rate. Nonetheless, this community-based study has demonstrated that TOT can lead to a statistically significant improvement in healing rates in patients with DFUs that are resistant to healing with optimal SOC alone [15].…”
Section: Topical Oxygen Effect On Wound Healing-the Evidencementioning
confidence: 76%
“…CDO devices apply topical continuous diffusion of non-pressurized (normobaric) pure oxygen through small cannulas or thin tubes to semi-occlusive or proprietary wound dressings. Small portable, battery powered, electrochemical oxygen generators supply a continuous flow of pure oxygen over the wounds 24 h per day at a flow rate of up to 15 mL/h [13][14][15]. An oxygen gradient then develops between the overlying dressing and the wound bed, thereby facilitating oxygen diffusion.…”
Section: Topical Oxygen Devicesmentioning
confidence: 99%
See 2 more Smart Citations